Estudio del Trazado Geométrico y Estructural de la vía desde, La Comunidad Santa Martha – Muyuyacu – hasta Armijos las Brisas; del Cantón Camilo Ponce Enríquez, Provincia del Azuay. - Guerrero Bermeo, Juana Isabel (2015)
techniques and unstable anti pathway from, Santa Martha Community features - Muyuyacu - up Armijos the Brisas; Canton Camilo Ponce Enríquez, constitutes a risk to the surrounding community members and to those who pass, which is to the detriment of socio - economic development of the area. The main objective of this project is to perform studies of geometric design and structural design of the track from the Community Muyuyacu Santa Martha continues to Armijos the Brisas; Canton Camilo Ponce Enríquez Azuay Province, to contribute and improve later execution. The methodology used for this study is based on research through literature sources, consultations, exploratory research and surveying to know the physical characteristics of the study area activities. This project was designed according to the needs of the sector, optimizing resources to make the project environmentally and economically feasible during construction and during its useful life, the length of the track is 5013.32 m, being a road IV order according to the classification of MTOP, the same throughout its development has 7 reinforced concrete box culverts and side ditches either side of the road type. It is recommended to meet the specifications and design standards given by the MTOP, as well as applying the environmental management plan during and after construction of the road